Cadmium tolerance is associated with tissue-specific plasticity of metallothionein gene expression in Gammarus fossarum field populations - Auréline Lalouette; Arnaud Chaumot; Louveline Lepeule; Karen Gaget; Nicolas Delorme; Laura Garnero; Federica Calevro; Davide Degli Esposti (Scientific Reports)
Abstract The metallothionein gene family codes for proteins involved in metal homeostasis and acute detoxification of non-essential toxic metal ions across the tree of life. We have previously documented increased cadmium (Cd) tolerance in field populations of the crustacean Gammarus fossarum exposed to chronic metallic contamination of geochemical origin. This tolerance is lost during maintenance of organisms in the laboratory, and is transmitted to offspring via parental effects. This study investigated whether the expression of the Cd-responsive metallothionein gene mt1 could be related to Cd-tolerance plasticity in G. fossarum. In eleven populations with different chronic Cd exposure history, we simultaneously assessed Cd-tolerance (mortality tests) and G. fossarum mt1 expression levels by RT-qPCR in the gills and caeca of adult males and in neonates. mt1 expression levels in the two organs were correlated to Cd-tolerance in field organisms and a loss of tolerance was observed in parallel with a decreased expression of mt1 in the caeca after maintenance in uncontaminated water. We also recorded a greater inducibility of mt1 expression in offspring of tolerant populations in the laboratory when re-exposed to Cd along with the bi-parental transmission of Cd-tolerance. These results suggest that the control of mt1 expression is involved in the plasticity of Cd-tolerance in gammarid populations with different histories of Cd exposure.